2017
DOI: 10.1159/000480665
|View full text |Cite
|
Sign up to set email alerts
|

Body Weight Changes after Deep Brain Stimulation for Obsessive-Compulsive Disorder or Depression

Abstract: Background: In 2010, we published an often-cited case report describing smoking cessation and substantial weight loss after deep brain stimulation (DBS) for obsessive-compulsive disorder (OCD) in an obese patient. To test whether this single observation was also observed in the treated population at large, the weight changes of a larger cohort of patients who underwent DBS for OCD or major depressive disorder (MDD) were studied. Results: Data were available for 46 patients (30 OCD and 16 MDD patients; mean age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Finally, because of its assumed role in reward-related behavior, the ventral anterior limb of the internal capsule (vALIC) could be a potential target for obesity DBS. However, Linssen et al (2017) reported no significant change in body weight on a group level after vALIC DBS (mean follow-up was 3.8 years, range 10 months to 8.7 years) for either obsessive-compulsive disorder ( n = 30) or major depressive disorder ( n = 16). The average baseline BMI in their sample of 46 patients was 28.0 (SD 7.3), with 26 (57%) being overweight (BMI 25–30, n = 11), obese (BMI 30–40, n = 12), or morbidly obese (BMI ≥ 40, n = 3).…”
Section: Nucleus Accumbens Dbsmentioning
confidence: 98%
“…Finally, because of its assumed role in reward-related behavior, the ventral anterior limb of the internal capsule (vALIC) could be a potential target for obesity DBS. However, Linssen et al (2017) reported no significant change in body weight on a group level after vALIC DBS (mean follow-up was 3.8 years, range 10 months to 8.7 years) for either obsessive-compulsive disorder ( n = 30) or major depressive disorder ( n = 16). The average baseline BMI in their sample of 46 patients was 28.0 (SD 7.3), with 26 (57%) being overweight (BMI 25–30, n = 11), obese (BMI 30–40, n = 12), or morbidly obese (BMI ≥ 40, n = 3).…”
Section: Nucleus Accumbens Dbsmentioning
confidence: 98%
“…Notably, there is scarce systematic data on the effects of VS/VC DBS on weight. In a retrospective study, Linssen and colleagues [9] did not observe weight change after DBS of the ALIC. In this study, data from different time points of observation for each patient were pooled, whereby the follow-up period ranged from 10 months to 8.7 years, making it difficult to draw clear conclusions from the study.…”
Section: Introductionmentioning
confidence: 99%